The Effectiveness of Blended Learning Oriented LKS with POGIL Strategy on High School Chemical Bond Subject - Siti Lailatul Mufarohah; Kusumawati Dwiningsih (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
The rapid development of technology requires innovation in learning. One of the innovations is blended learning. The concept of blended learning is mixing of face-to-face learning model in the classroom with online learning. The blended learning will strengthen the conventional learning model conducted in the classroom through the development of education technology. Blended learning can be combined with constructivist and cooperative learning using POGIL strategy. POGIL contextual- based blended learning is suitable for chemical bonding subject because it has abstract characteristics involves atoms and electrons which are macroscopic, microscopic, and symbolic particles. The aim of this research is to create the effective student worksheet blended learning-based viewed from students pretest and posttest results. The development of model in student worksheet uses 4D models (four D models) from Thiagarajan which consists of 4 development stages: Define, Design, Develop, and Disseminate. Focus of this study was limited to the stage of develop. The data were collected using a test sheet in the form of pretest and posttest through a limited trial. The results of this research indicate that the usage of blended learning-based student worksheet is effective viewed from N-gain which was obtained as much as 86.67% of students achieving moderate criteria, 6.67% of students achieving high criteria, and 6.67% students reach low criteria.